Improving the Efficiency of Community Waste and Hazardous Waste Management According to the 3Rs Principle, Tha Sai Subdistrict Administrative Organization Samut Sakhon Province - Donjunla, Atthachai; Khitkhulnamchai, Sudabhorn (Rajapark Journal, 2025)
This research aimed to 1) study the efficiency of community hazardous waste and hazardous waste management according to the 3Rs principle in the Tha Sai Subdistrict Administrative Organization, Samut Sakhon Province, and 2) study the guidelines for increasing the efficiency of community hazardous waste and hazardous waste management according to the 3Rs principle in the Tha Sai Subdistrict Administrative Organization, Samut Sakhon Province. This research employed a qualitative approach, utilizing document analysis and in-depth interviews with 21 key informants. The data collection tools used were document analysis and in-depth interviews. Data were analyzed using a triangulation process, followed by data interpretation and inductive conclusions. The content analysis was conducted on the documents and interviews. The results of the research found that 1) community hazardous waste management requires the creation of good knowledge and understanding among the public, and disposal must be done systematically and safely according to the 3Rs principle to achieve maximum efficiency in reducing the amount of hazardous waste and preserving the environment. And 2) Guidelines for increasing the efficiency of community hazardous waste and hazardous waste management using the 3Rs principle focus on reducing waste and promoting the reuse of materials. In this regard, a combination of methods should be employed to dispose of waste, such as burning or converting it into fertilizer, along with public education to inform the public about proper waste separation and management. This approach aims to reduce the environmental impact and promote sustainable community health in the long term.